2020
DOI: 10.7150/jca.48357
|View full text |Cite
|
Sign up to set email alerts
|

Type-specific Distribution of Cervical hrHPV Infection and the Association with Cytological and Histological Results in a Large Population-based Cervical Cancer Screening Program: Baseline and 3-year Longitudinal Data

Abstract: Objectives: This study aimed to describe the study design, and to analyze the type-specific distribution of cervical high-risk human papillomavirus (hrHPV) infection and its association with cytological and histological results in a large population-based screening program in Buji Street, Shenzhen, China. Methods: A total of 10,186 women aged 21-70 years were co-tested by Cobas4800 HPV assay and liquid-based cytology. Women were referred to colposcopy by virtue of being HPV16/18-positive, Other hrHPV-positive/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…The findings above support the crucial role of extended genotyping in cervical screening [8], and provide evidence for the development of new technology for the detection of HPV types. In addition, this study was conducted at three counties in Henan Province, China with a shortage of cytologists.…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…The findings above support the crucial role of extended genotyping in cervical screening [8], and provide evidence for the development of new technology for the detection of HPV types. In addition, this study was conducted at three counties in Henan Province, China with a shortage of cytologists.…”
Section: Discussionsupporting
confidence: 65%
“…Whether extended genotypes (hrHPV genotypes except for HPV16/18) should be considered for triage or not is still well worth investigating. Recently, we showed in a large study that 75.8% of abnormal cytology and 50.9% HSIL cytology were attributed to other hrHPV infection among HPV-positive women, and 62.7%/43.9% of CIN2/CIN3+ were caused by other hrHPV infection over 3-year follow-up [8]. Moreover, the introduction of vaccines could lead to the eradication of HPV16/18 [9][10][11], better understanding of extended genotyping provides information for establishing favorable screening policies following the introduction of vaccines [12].…”
Section: Introductionmentioning
confidence: 99%
“…Clearance of HPV infection is encouraging alternative to eliminate ICC. Our and other prospective observational studies indicated that 85%, 50% and 5-10% of HPV infections could be cleared spontaneously in cervical intraepithelial neoplasia (CIN) 1, 2 and 3 respectively (4)(5)(6). Nevertheless, mechanisms of natural HPV clearance were largely unknown.…”
Section: Introductionmentioning
confidence: 84%
“…Women who are NILM but positive for HR-HPV account for most of the subjects with positive screening results encountered in routine practice, ranging from 6.7 to 14.9% (15)(16)(17)(18). In the overall population, the distribution of HPV genotypes in a decreasing order of frequency is 16, 52, 31, 51, 18, 58, 39, 33, and 59 (19).…”
Section: Challenges Overall Prevalencementioning
confidence: 99%
“…The results are presented in Table 1. A systematic review of 42 African studies testing for HPV infection in 17,273 women who were NILM (mostly from eastern Africa, with some from western, southern, and northern Africa) found that the most common HPV genotypes were HPV16, 52,35,18,58,51,45,31,53, and 56 in descending order (24). However, there were wide region-based variations in HPV infection rates.…”
Section: Challenges Overall Prevalencementioning
confidence: 99%